Penentuan jumlah produksi kimbab berdasarkan jumlah permintaan dan persediaan menggunakan metode Fuzzy Mamdani - Rafifa, Caltha; Safitri, Fadila Dian; Wiyanto, Andika; Rahmadhani, Dibaia Sarah; Masruri, Ihsan; Irawan, Suhendi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Nanda Kitchen is a home-based cafe that produces various kinds of Korean specialties, specifically kimbab. The large demand for kimbab signifies that Nanda Kitchen is frequently engaged to the stockouts of raw material supplies. Thus, kimbab production is unable to fullfil consumer’s demand. The intention of this research is to ascertain the appropriate amount of kimbab production. Effective demand forecasting is required to fullfil customer’s demand by sufficient raw material supplies. Demand forecasting was carried out using POM-QM for Windows with Moving Average (n=3) and Exponential Smoothing (alpha 0.3 and 0.5). The lowest error value is taken to implement Fuzzy Mamdani (MATLAB). Exponential Smoothing (?=0.5) is most proper method for forecasting demand (error value of 7.6%). Nanda Kitchen needs to produce 1460 kimbabs with input demand of 1473 and raw material supply of 2470 based on Fuzzy Mamdani.